Tata Kelola Kolaboratif dalam Pengelolaan Sport tourism untuk Meningkatkan Ekonomi Lokal di Musi Banyuasin Indonesia - Fariz, Muhammad; Lionardo, Andries; Chendra, Rudy; Nasution, Chairika (Universitas Medan Area, 2026)
This study aims to analyze the implementation of collaborative governance in sport tourism management and its contribution to local economic development in Musi Banyuasin Regency. This research employs a qualitative approach with a case study design using interviews, observations, and documentation. The findings indicate that sport tourism has contributed to local economic activities, including increased business opportunities and local income, although the impacts remain temporary and unevenly distributed. From a governance perspective, collaborative governance has involved government, private sector, and community actors, yet it has not been optimally implemented. Key challenges include weak alignment of goals, dominance of leadership, ineffective communication, and limited resource sharing. This study proposes an enhanced collaborative governance model by incorporating the Interaction and Involvement Actor (IIAT) dimension to strengthen actor interaction and participation. This model is expected to improve the effectiveness and sustainability of sport tourism management.